A comparison of trends in opioid dispensing patterns between Medicaid pharmacy claims and prescription drug monitoring program data. Issue 9 (10th August 2020) - El Ibrahimi, Sanae; Hallvik, Sara; Johnston, Kirbee; Leichtling, Gillian; Choo, Esther; Hartung, Daniel M.
Abstract: Purpose: Public and private payers have implemented benefit limitations to reduce high‐risk opioid prescriptions. The effect of these policies on the increase of out‐pocket payment is unclear. To understand this gap, we compared the discrepancies in trends between opioid prescription fills vs claims among Medicaid beneficiaries. Methods: Data from the Oregon Prescription Drug Monitoring Program (PDMP) and Oregon Medicaid administrative claims were used to identify Medicaid beneficiaries 18 years and older enrolled at least one full month from 2015 to 2017. Generalized linear models assessed the trends in the monthly rates of opioid PDMP prescription fills and pharmacy claims per 1000 eligible members. Rates by morphine equivalent dose (MED) tier (<50, 50‐89, 90‐120, >120 MED) and co‐prescribed opioid and benzodiazepine were also assessed. Results: During the study period, an average of 495 355 Medicaid members had 2 797 054 opioid PDMP fills and 2 472 155 opioid Medicaid pharmacy claims. Study participants had 15.4 (95% confidence interval [CI] 13.6 to 17.0; P < .001) more prescriptions per 1000 member per month in the PDMP data (114.1 [ SD 7.4]) compared with the Medicaid claims data (98.7 [ SD 7.9]). Similarly, there were 1.9 more co‐occurring opioid/benzodiazepine prescriptions per 1000 members per month observed in the PDMP data than the Medicaid claims data (95% CI 1.7 to 2.1; P < .001). At each MED tier, the PDMP fills were consistently higher than the claims ( P < .001). Conclusions: Higher rate of fills in the PDMP compared to pharmacy claims suggests that there may be an increasing trend of out‐of‐pocket payment among Medicaid beneficiaries.